#1**+2 **

my answer

\(y=log_bx\qquad \\ \text{Make x the subject}\\ b^y=b^{log_bx}\\ b^y=x \text{swap x and y over to find the inverse function}\\ b^x=y\\ y=b^x \)

So I have determined that the second funtion is the inverse of the first one.

So this means that they are reflections of one another across the line y=x

so draw the line y=x and reflect each ot the points across it and you will have the points for the second graph.

So

(1,0) becomes (0,1)

(2,1) becomes (1,2)

etc

Melody
Apr 1, 2017

#1**+2 **

Best Answer

my answer

\(y=log_bx\qquad \\ \text{Make x the subject}\\ b^y=b^{log_bx}\\ b^y=x \text{swap x and y over to find the inverse function}\\ b^x=y\\ y=b^x \)

So I have determined that the second funtion is the inverse of the first one.

So this means that they are reflections of one another across the line y=x

so draw the line y=x and reflect each ot the points across it and you will have the points for the second graph.

So

(1,0) becomes (0,1)

(2,1) becomes (1,2)

etc

Melody
Apr 1, 2017